Uncommon defibrinogenation and coagulopathy caused by Trimeresurus stejnegeri stejnegeri envenomation in a patient with swelling above the ankle. (15th October 2022) - Chen, Yu-Hsin; Mao, Yan-Chiao; Liu, Po-Yu; Chiang, Liao-Chun; Chen, Wei-Yu; Lai, Chih-Sheng; Ho, Cheng-Hsuan; Chen, Kuang-Ting; Lin, Wen-Loung; Wen, Cheng-Yang
Abstract: In Taiwan, Trimeresurus stejnegeri stejnegeri (Stejneger's Bamboo pitviper) is responsible for more than half of all venomous snakebites annually. This species often causes local envenoming characterized by tissue swelling and pain, occasional local ecchymosis, bullae and blister formation, and lymphangitis and lymphadenitis. The pathophysiology and treatment of potentially life-threatening coagulopathy and defibrinogenation induced by T . s . stejnegeri systemic envenoming have not been specifically addressed. Here, we describe the case of a man who was bitten by T . s . stejnegeri on his right first toe, which later developed into swelling above the ankle. It was found that there was severe hypofibrinogenemia, prolonged prothrombin time, and reduced activities of factors V and XI, plasminogen, and α2-antiplasmin. Even though a favorable outcome was achieved after repeatedly administering specific antivenom, fresh frozen plasma, and cryoprecipitate, probably low effectiveness of antivenom against the coagulopathy and prodigious amounts of replacement products were observed. To control coagulopathy early and avoid the needless replacement of coagulation factor, which are associated with inherent adverse reactions, more frequent serial blood assessment (e.g., every 6 h) and higher initial antivenom doses may be helpful. Knowledge of the specific coagulation factor deficiencies may improve our understanding of the relationship between hemotoxins and the resulting envenoming syndromes in this snakebite. Graphical abstract: Image 1 Highlights: Defibrinogenation and coagulopathy caused by Trimeresurus stejnegeri bite have uncommonly been reported. We observed hypofibrinogenemia and reduced activities of factors V and XI, plasminogen, and α2-antiplasmin after the bite. A repeated administration of a specific antivenom and blood component replacement was performed to treat the patient. Frequent blood assessments and large initial antivenom doses may help achieve early control of coagulopathy. Coagulation factors and fibrinogen levels should be included to better evaluate consumptive coagulopathy.